Subjects with cardiovascular disease or high disease risk are more sedentary and less active than their healthy peers. Issue 1 (2nd May 2018) - Vasankari, Ville; Husu, Pauliina; Vähä-Ypyä, Henri; Suni, Jaana Helena; Tokola, Kari; Borodulin, Katja; Wennman, Heini; Halonen, Jari; Hartikainen, Juha; Sievänen, Harri; Vasankari, Tommi
Abstract : Objectives: We investigated differences in objectively measured sedentary behaviour (SB) and physical activity (PA) levels in subjects with cardiovascular disease (CVD) diagnosis or high CVD risk compared with healthy controls. Methods: The present study includes a subsample (n=1398, Health 2011 Study) of participants, who attended health examinations and wore a triaxial accelerometer (≥4 days). Patients with CVD were identified and CVD risk was calculated for others using Framingham Risk Score (FRS). Participants were categorised into groups: FRS<10%; FRS=10%–30%; FRS>30%/CVD. Raw acceleration data were analysed with mean amplitude deviation (MAD) and angle for posture estimation (APE). MAD corresponding to intensity of PA was converted to metabolic equivalents (MET) and categorised to light (1.5–2.9 METs) and moderate to vigorous PA (MVPA≥3.0 METs). APE recognises SB and standing. Results: Daily accumulated time of >30 s MVPA bouts was higher in FRS<10% group (46 min) than in FRS>30%/CVD group (29 min) (p<0.001). FRS>30%/CVD group were more sedentary, their mean daily number of >10 min SB bouts (13.2) was higher than in FRS <10% group (11.5) (p=0.002). Conclusion: Number and accumulated times of SB and PA bouts differed between the CVD risk groups. Causative research is required to assess the importance of SB and PA in prevention and rehabilitation of CVDs.